Experimental Study on Manager Ethical Evaluation Towards Earnings Management and its Consequences - Lodovicius Lasdi (The Indonesian Journal of Accounting Research, 2013)
Recent research on earnings management has generally not examined the specific ethical dilemma that arises when a choice to engage in earnings management results in positive organizational consequences. This study focuses on the consequences of earnings management behavior in response to the positive organizational consequences of earnings management that justify the means of earnings management. This experimental research design uses 2x2 between subjects to investigate manager evaluations of, and reactions to, a scenario in which a hypothetical employee makes a choice whether or not to engage in earnings management, with consequences that are either favorable or unfavorable to the organization. The results indicate that managers may be motivated to discount the ethical impact of earnings management when the consequence has a favorable impact on the organization. This finding has implication for corporate governance in the organization to establish a strong ethical tone throughout the organization.